Stakeholder power towards corporate social and environmental responsibility disclosure : evidence from Malaysia - Noradiva Hamzah; Maizatulakma Abdullah (Penerbit Universiti Kebangsaan Malaysia, 2018)
The purpose of this study is to explore stakeholder power in corporate social and environmental responsibility (CSER) disclosure in Malaysia. We collected data through content analysis and semi-structured interviews. Content analysis was used to identify the disclosure level of CSER in the annual reports by listed companies in Malaysia. Then, semi-structured interviews were conducted to collect opinions from stakeholders to understand the CSER phenomenon, particularly the motivations of CSER in Malaysia. This study utilises the ‘stakeholder theory’ because this theory is based on the moral treatment of stakeholders and has been widely used by accounting researchers in CSER sustainability studies. The interviews provide evidence that stakeholders, particularly government and non-government organisations, show their concern on the importance of social and environmental disclosures. This concern may be one of the driving factors that influence companies to reveal a large amount of CSER information related to the society and environmental aspects. This finding indicates that present secondary stakeholders play a crucial part in compelling organisations to disclose CSER information.